"No future for Libya with Gaddafi": Classical realism, status and revenge in the UK intervention in Libya. Issue 3 (19th July 2022) - Dawson, Grant
Abstract: Why did Britain intervene in Libya in 2011? Several explanations suggest themselves: security, R2P and status. The article shows that status was a significant motivating factor, and this demonstrates a dynamic that helps to refine a classical realist theory of intervention. The article calls for status to be seen intrinsically and instrumentally, and for more attention to be paid to the related motive of revenge. The findings suggest (though do not prove from a causal standpoint) that status may be a stronger motive than security for state decision-makers. The article's central empirical argument is that regime change in Libya was not the last stage of Britain's foreign policy of intervention. Rather, intervention was the last stage in Britain's status and revenge-driven foreign policy of regime change. Britain saw the Libya crisis as a chance to preserve its great power status and revenge Muammar Gaddafi for past wrongs.